Advances in Understanding of Taurine Functions in Fishes Across Species and Life Stages - P. Salze, Guillaume; Davis, D. Allen; Resley, Matthew; Rhody, Nicole; Maine, Kevan; Stuart, Kevin; Drawbridge, Mark (Facultad de Ciencias Biologicas, 2015)
Taurine is now widely recognized as an essential nutrient in many teleost species, and during the past decade investigations have focused on determining quantitative requirement levels and physiological and metabolic responses to dietary taurine. Although the current state of knowledge is biased toward high-value marine carnivorous species, evidence points to functional differences among species (e.g., bile salt conjugation, osmoregulation, membrane stability). Prediction of the qualitative or quantitative requirement based on ecological boundaries is difficult, although trophic level seems to be a better predictor even if several exceptions exist. Thus caution must be exerted when assuming the qualitative or quantitative taurine requirement in a given species. Additionally, a number of studies highlight changes in the quantitative requirement between life stages, particularly in larval stages. If knowledge of taurine functions and potential technological uses in larval stages is limited compared to juvenile stages, it is even scarcer in reproducing broodstocks. Consequently, the first part of this paper reviews the current understanding of the species- and life stage-dependent differences in in taurine function and requirement levels. In a second part, initial experimental results obtained in California yellowtail Seriola lalandi and Florida pompano Trachinotus carolinus broodstocks are presented. While the crucial importance of essential fatty acid in egg quality and overall reproduction performances needs no additional proof, results highlight the importance of proteins as well. In this context, not only were the total amount of protein and amino acid levels correlated with hatching success, but results also suggest the relationship between urea cycle and survival to 1st feeding in the newly hatched larvae.